Promoting Sustainable Fashion Through Ergonomics: A Bibliometric Study On Textiles And Garments (Journal of Namibian Studies : History Politics Culture, 2023)
Promoting sustainable fashion via the incorporation of ergonomic concepts in the realm of textiles and clothing has received a lot of attention in recent years. By analysing relevant articles, this bibliometric research seeks to offer an overview of the scientific environment around this issue. This research identifies and evaluates major sources that contribute to the knowledge and promotion of sustainable fashion practises via ergonomics using bibliometric analysis methodologies. The research uncovers a number of notable publications that address different areas of sustainable fashion, including as design considerations, manufacturing procedures, supply chain optimisation, and user comfort. The results provide important insights into the present state of research and show the importance of ergonomics in promoting sustainability in the fashion industry. This study will aid researchers, students, and industry professionals by providing a complete overview of the most significant sources and developing trends in promoting sustainable fashion via ergonomics in the textiles and garments area.